Experimental study on drilling process of a newly developed CFRP/Al/CFRP co-cured material. (March 2022) - Zhong, Bingfu; Zou, Fan; An, Qinglong; Chen, Ming; Zhang, Hongzhou; Xie, Changsong
Abstract: The drilling is often applied for a newly developed CFRP (carbon fiber reinforced plastic)/Al/CFRP co-cured material to ensure excellent fastening and accurate assembly. However, because of their different material properties, there are great challenges in one-time drilling of CFRP/Al/CFRP co-cured materials. This paper presents contrast between the TiAlN coating and uncoating for the quality/accuracy of drilling CFRP/Al/CFRP co-cured materials. Considering inhomogeneous behavior, a three-dimensional drilling model is proposed to analyze the drilling process. Then, experiments are taken to prove the effect of the TiAlN coating on the thrust force of the drill bit. Finally, the results show that it helps reduce the maximum thrust force, and improving hole edge quality, surface morphology and roughness during the drilling process of CFRP/Al/CFRP co-cured materials.